Effect of the addition of Fe3O4 nanoparticles on the performance of polyethersulfone nanofiltration membrane for the rejection of 54,56Mn ions from aqueous solution - Sedigheh Daroumi; Mohammad Ali Aroon; Ramin Yavari; taher yousefi; Hossein Ghasemi mobtaker (Journal of Water and Environmental Nanotechnology)
In this study, the flat sheet membranes including the neat polyethersulfone (PES) and the mixed matrix membranes (MMMs) containing 20 wt. % polyethersulfone (PES) and various amounts of Fe3O4 nanoparticles were prepared using wet phase inversion and conventional casting methods. Manganese ion rejection and permeate flux as a performance evaluation of the prepared membranes was studied and compared. The characteristics of the fabricated membranes and the synthesized nanoparticles were fulfilled by transmission electron microscopy, field emission scanning electron microscopy and contact angle measurement. The operational parameters such as polymer concentration, pressure, pH, manganese ion concentration and time for manganese ion rejection and permeability were firstly optimized on the neat PES membrane. In the next steps, the performance of the fabricated MMMs containing various amount of Fe3O4 nanoparticles and PES (20%wt.) was evaluated and compared under these optimized conditions. Under the optimal conditions obtained for the rejection of manganese ions by neat PES, the fabricated MMMs had better performance than the neat PES membrane. Also, the results showed that the best performance of the prepared MMMs with the manganese rejection percentage of 89.3% and permeate flux of 28.7 L.m-2.h was found to belong to the PES membranes containing 0.1 wt.% of Fe3O4.